ANALISIS MAKNA SOUNDTRACK LAGU “DREAMERS” OLEH JUNGKOOK BTS PADA PIALA DUNIA 2022 - Shinta Rahayu Melyana; Deswita Aminatuz Zahara (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
Jungkook appeared by singing the official World Cup soundtrack entitled Dreamers with singer and song producer from Qatar, Fahad Al-Kubaisi. The purpose of this study was to investigate the meaning of the Dreamers soundtrack and related reasons for choosing Jungkook to appear singing the official World Cup soundtrack through the literature review method. The findings show that in general it is effective because there are things in the TEAR indicator and related to the slogans of this World Cup, such as multiculturalism, diversity and peace.